Die Welt gehört uns - SPD - Bonn-Sequenz/Bavaria; Sozialdemokratische Partei Deutschlands (SPD), Vorstand, Referat Öffentlichkeitsarbeit, Bonn; Courir-Druck, Bonn (1992)
Bemerkungen: Wandzeitung 2, 1992